2012
DOI: 10.1186/1758-2555-4-42
|View full text |Cite
|
Sign up to set email alerts
|

Nature and incidence of upper limb injuries in professional cricket players a prospective observation

Abstract: IntroductionCricket is the most popular sport in India, and is gaining in importance in all south-east Asian countries. The purpose of this study was to prospectively investigate the incidence, nature, and site of acute upper limb injuries sustained by professional cricketers of north India over a period of one year.Material & methods95 cricket players (mean age 18.9 years) were prospectively evaluated for nature and incidence of upper limb injuries from 1st November 2008 to 31st October 2009. For the purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…Ours was a different methodology, as our calculations were based mainly upon injuries sustained during practice and involved a larger number of younger players (under 19 and under 17); the total number of playing hours also included the time spent in physical training, which was not factored in the other studies. 1 Some aspects of playing cricket were noted to be unique to India; we found that most of our players continued to practice or play cricket during the so-called "off season" (summer months) also; thus, the total playing time becomes much more in these circumstances, during one calendar year. We also suggested that international players anyway play more intense matches, with more competitive strains, and this may be one of the reasons for higher injury rate in the international studies.…”
Section: Jpmermentioning
confidence: 88%
See 2 more Smart Citations
“…Ours was a different methodology, as our calculations were based mainly upon injuries sustained during practice and involved a larger number of younger players (under 19 and under 17); the total number of playing hours also included the time spent in physical training, which was not factored in the other studies. 1 Some aspects of playing cricket were noted to be unique to India; we found that most of our players continued to practice or play cricket during the so-called "off season" (summer months) also; thus, the total playing time becomes much more in these circumstances, during one calendar year. We also suggested that international players anyway play more intense matches, with more competitive strains, and this may be one of the reasons for higher injury rate in the international studies.…”
Section: Jpmermentioning
confidence: 88%
“…1 Most of the previously published epidemiological studies on cricket injuries have come from South Africa, Australia, and England, particularly at the elite level.…”
Section: 5005/jp-journals-10028-1208mentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the recently published studies on upper injuries in cricketers, Dhillon et al 11,12 looked at 95 players of the Punjab Cricket Association; this included eight wicketkeepers, and three injuries were seen in these wicketkeepers, with one serious hand injury ( Table 2). The overall incidence of injuries to wicketkeepers was noted to be 7%.…”
Section: Review Of Literaturementioning
confidence: 99%
“…There has been research at grassroot level on the incidence of upper limb injuries sustained by professional cricketers of North India, 20 cause of chronic low back pain in a young Indian fast bowler, 21 exploring the connection between hand grip strength and anthropometric variables in district cricketers, 22 examining the effects of sleeper's stretch on glenohumeral internal rotation and horizontal adduction range of movement in male elite cricket bowlers from Southern India 23 and investigating the effect of body composition on VO 2 max in under-19 and under-16 male cricket players. 24 Additionally, research has been conducted on university level cricket players testing their physical fitness levels, 25 investigating the correlation between back strength and leg strength 26 and comparing the anxiety levels of male university cricket players across different universities during sporting competitions.…”
Section: Sports Medicine and Indian Cricketmentioning
confidence: 99%